The Effect of Household Consumption and Government Expenditure on Economic Growth in South Sulawesi 2016 - 2020 Periode - Ramli, Muh.; Dangkeng, Arianto; Sudirman, Nengsi; Nurfaisah, Nurfaisah; Rifqiansyah, Rifqiansyah; wijaya, Hasrul; munir, Rahim (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the effect of household consumption and government spending partially on the economic growth of South Sulawesi and to determine the dominant variable affecting the economic growth of South Sulawesi. The type of research that is used is quantitative with econometric approach, the data used is time series data obtained from BPS of South Sulawesi province from 2016 until 2020. Data analyzed using multiple regression which though with SPSS 23 program. Based on the analysis of household consumption to Per Capita GRDP in South SulawesI during the period of 2016 to 2020 shows the value of t-count larger than t-table that is 21.469> t table 4.302 with probability value 0.002 below 0.05 or 5% means consumption variable households have a positive and significant impact on Per Capita GRDP in South Sulawesi. Based on the result of analysis of government expenditure to Per Capita Gross Regional Domestic Product in South Sulawesi period 2012 to show that t value is calculated more kecill than t table that is -0,063 <t table 4,302 with probability value 0,956 above 0,05 or 5% meaning government expenditure variable have negative effect and not significant to Per Capita GRDP in South Sulawesi. Based on the analysis, the dominant variable affecting the economic growth of South Sulawesi is household consumption, it can be seen from the beta value of 1.002 bigger than other beta value.